Study on presentation and predisposing factors for pediatric deep neck space infection - Singh, Mukesh Kumar; Ghosh, Pritha; Maitra, Mainak (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Aim were to study the clinical presentation and predisposing factors in children with deep neck space infections and to study the effective mode of management of pediatric deep neck space infections and its complications. Methods: This prospective study was done in a tertiary care hospital on 163 pediatric patients with deep neck space infections who were thoroughly examined to know the source of the infection. Ultrasonography of neck and Radiological investigations were done to determine the location and extent of the abscesses. All patients were started on empirical antibiotic therapy of amoxicillin and clavulanic acid and metronidazole. Patients with small abscess were blindly aspirated with wide bore needle, while incision and drainage were done for large abscess. The pus samples from both were sent for culture and sensitivity. Patients presenting with complications, underwent incision and drainage. Patients, who failed empirical antibiotic therapy and needle aspiration, then underwent incision and drainage. Results: The most common symptom and sign was neck swelling (85%). The next most common symptom was neck pain (70%). Most of the patients had unknown source of infection and others had history of recurrent sore throat, dental infections, acute cervical lymphadenopathy, parotitis and furuncle over neck. Conclusions: Deep neck space infections (DNI’s) in pediatric population constitutes of medical emergency as it could lead to life threatening complications in a short time. Though with changing times of new diagnostic and therapeutic tools have drastically reduced the incidence of complications.